2007
DOI: 10.1200/jco.2006.07.3890
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Contralateral Prophylactic Mastectomy in Newly Diagnosed High-Risk Breast Cancer Patients Who Underwent BRCA1/2 Gene Testing

Abstract: With respect to quality of life and distress, patients who choose CPM fare as well as those who do not in the first year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 36 publications
(11 reference statements)
5
57
1
2
Order By: Relevance
“…Previous observational studies support this position. 4,26 Finally, the results of the per-protocol analyses need to be interpreted with a great deal of caution, given the limited sample size available for these analyses and the concomitant limitations in the ability to detect statistically and clinically relevant differences in psychosocial outcomes. Larger studies are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous observational studies support this position. 4,26 Finally, the results of the per-protocol analyses need to be interpreted with a great deal of caution, given the limited sample size available for these analyses and the concomitant limitations in the ability to detect statistically and clinically relevant differences in psychosocial outcomes. Larger studies are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…1 Between 18 and 29% of carriers with a favorable prognosis opt for immediate or, more often, delayed contralateral prophylactic mastectomy (CPM) to reduce their risk of a second breast cancer. [2][3][4] Several studies have shown that a CPM leads to a large reduction (up to 95%) in the risk of contralateral breast cancer, with increasing evidence of improved breast cancer-specific survival. 5,6 Advances in the technology and logistics of genetic testing of the BRCA1 and BRCA2 genes have made it possible to offer high-risk breast cancer patients the opportunity to undergo rapid genetic counseling and testing (RGCT) during the time period between diagnosis and primary surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Several clinical studies have sought to understand the emotional impact on women who have undergone prophylactic surgery to eliminate cancer risk. 40 Those who opted for surgical methods reported more distress about their mutation carrier status than those who decided on medical surveillance and, in both the short and longer term, although their cancer risk worry was significantly reduced, their level of anxiety remained higher than for the surveillance group. 41 In other words, predictive genetic knowledge appears to be more worrisome for those with a propensity towards anxiety in general.…”
Section: Psychological and Counselling Studies: Decision-making Arounmentioning
confidence: 90%
“…Some studies showed that psychosocial effects and quality of life were similar in patients with and without prophylactic mastectomy (24)(25)(26), whereas other studies indicate that it has a negative impact on body image and sexuality (24)(25)(26). Therefore, when choosing the most appropriate surgical treatment for breast cancer in mutation carriers, psychosocial aspects should also be taken into consideration.…”
Section: Psychosocial and Emotional Effects Of Prophylactic Mastectomymentioning
confidence: 99%